2021
DOI: 10.1021/acsami.1c03699
|View full text |Cite
|
Sign up to set email alerts
|

Microporous Layer Containing CeO2-Doped 3D Graphene Foam for Proton Exchange Membrane Fuel Cells at Varying Operating Conditions

Abstract: To improve the interfacial mass-transfer efficiency, microporous layers (MPLs) containing CeO2 nanorods and the CeO2 nano-network were prepared for proton exchange membrane fuel cells (PEMFCs). In order to minimize the contact resistance, the three-dimensional (3D) graphene foam (3D-GF) was used as the carrier for the deposition of CeO2 nanorods and the nano-network. The CeO2-doped 3D-GF anchored at the interface between the catalyst layer and microporous layer manufactured several novel functional protrusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…The respective conductivity data were evaluated from the Nyquist plot with the help of half circular curves through curve fitting. The equivalent circuit for the analysis of EIS and the representative Nyquist plot are illustrated in Figure S9. , As observed from Figure a, the proton transport ability of the respective film showed an upward fashion with RH. For the in-plane direction, at 40% RH and 25 °C, 3DGO yielded a σ-value of 9.80 × 10 –4 S cm –1 with respect to 1.7 × 10 –1 S cm –1 at 90% relative humidity.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The respective conductivity data were evaluated from the Nyquist plot with the help of half circular curves through curve fitting. The equivalent circuit for the analysis of EIS and the representative Nyquist plot are illustrated in Figure S9. , As observed from Figure a, the proton transport ability of the respective film showed an upward fashion with RH. For the in-plane direction, at 40% RH and 25 °C, 3DGO yielded a σ-value of 9.80 × 10 –4 S cm –1 with respect to 1.7 × 10 –1 S cm –1 at 90% relative humidity.…”
Section: Resultsmentioning
confidence: 91%
“…GO forms a sheet-like graphene network by utilizing its various polar functional groups such as epoxy, carboxylic, and hydroxyl groups. These materials have gained extensive attention due to their extraordinary physical and chemical characteristics such as high conductivity and amazing mechanical strength, which are useful for application in various fields including proton conductors. The ion conduction primarily occurs by utilizing the epoxy groups throughout the edge and pinholes of the GO nanosheets. These sites can hold water molecules that construct the pathway for the conduction of proton using the Grotthuss mechanism. Moreover, the surface property of GO can be altered through chemical modification, which enhances the water retention ability of the functionalized GO materials.…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cells (PEMFCs), used as the energy-conversion device for converting the chemical energy of the fuel into electrical energy, have been applied in transportation, household power and distributed power stations, benefiting from their environmentfriendly, low-noise, high energy-conversion efficiency and quick start-up characteristics. [1][2][3] However, the high cost, insufficient durability and specific power still impede the commercialisation of PEMFCs. [4][5][6] The gas diffusion layer (GDL), employed between the flow field (FF) and the catalyst layer (CL), is a critical component of PEMFCs, which distributes the gas, drains the generated water in the cathode, supports CL and conducts electrons between the bipolar plate and the CL.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Thus, a dry technique is proposed to prepare MPL for PEMFCs with convenient operation, solvent-free and excellent reproducibility. 19,20 Researchers have endeavored to enhance fuel cells' performance in terms of fabricating new materials, 3,[21][22][23][24] constructing favorable structures 17,[25][26][27][28] and optimizing components of GDL. [29][30][31] From the material aspect, some studies have demonstrated the use of carbon fiber (CF), carbon nanotube and graphene in MPL to improve the electrical performance and gas permeability of PEMFCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation